THE ROLE OF (IT) GOVERNANCE FRAMEWORK'S DIMENSIONS IN LIMITING THE RISKS OF (CAIS): APPLIED TO INDUSTRIAL FIRMS IN IRAQ - Yasir Mohammed Ali Al-Wattar; Karrar Mohammed AL-Shafeay (Scholar Express Journal, 2023)
This research seeks to determine the dimensions of (ITG) that could reduce CAIS risks in Iraq industrial firms. This research used a snowball sample technique to collect data from 291 employees worked in Iraq industrial firms. The results showed that all dimensions of (ITG) (Firm & Planning, Acquire & Implementation, Delivery & Support, Monitoring & Evaluation, Guidance & Control) have an impact on the decrease of CAIS risks significantly and positively
Keywords: Information Technology Governance; Cloud Accounting Information Systems; risks